Feeding and greening the world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Feeding and greening the world: the role of international agricultural research by Derek Tribe 1994 274pp (pbk) ISBN 0 85198 920 9